Formation of Concepts of the Coordinate System in Primary School Students (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
This article describes the concepts of the coordinate system, their content in the program and textbooks on mathematics for elementary school, as well as the methods for forming the initial ideas about the subject in younger students.